OPTIMIZATION OF RESERVOIR OPERATION FOR HYDROELECTRIC POWER PLANT WITH HISTORICAL DISCHARGE RELIABILITY CONSIDERATIONS (Case Study: Sadawarna Reservoir Plan in West Java Province) - PUTRI RACHMANTY - NIM : 95015304 , RATIH
Hydroelectric power plants is a major additional function of water reservoir. In general the main function of reservoir are for irrigation and domestic raw water. In recent years, only large-capacity power plants have been built. But now renewable energy become main issue and hydroelectric power plants, in this case Micro Hydro Power Plant (PLTMH), is one of the solutions to produce electricity needs. Historical discharge of the Cipunagara River will be used in analysis to obtain the most optimal electricity production pattern and close to reality in the future because discharge pattern is repeated. Sadawarna Reservoir development plan in Cipunagara watershed, West Java, started from 2004 until now, in the final stage of land acquisition so that scheduled physical work can begin in 2018. The final review of the Sadawarna Reservoir design plan is set that crest spillway elevation at + 80.00m with volume 44.56 million m3. Sadawarna Reservoir is planned to provide irrigation water for 4,400Ha of paddy fields, domestic raw water of 2.56 m3 / second, maintenance flow of 3.6 m3 / second and flood control in the downstream of Cipunagara River. The purpose of this study is to devise optimization operating pattern of Sadawarna Reservoir by considering historical discharge reliability with choosing the best scenario from analysis for electrical energy production. Simulation method is carried out to optimize the demand-release setting in three scenarios. Scenarios 1 and 2 apply minimum volume variations at elevations of 60m and 65m with an initial volume of 40 million m3. While scenario 3 applies Total Annual Demand (TAD) efficiency by reducing the percentage of irrigation water requirements by 30% and domestic raw water by 20% based on minimum service standards. Dry season simulations in all three scenarios use a minimum limit requirement water shortage ratio of 30%. However, in reality this minimum limit cannot always be met. Changes to this boundary condition will impact to discharge release so that electrical energy production decreases and or the area of rice fields that are not irrigated increases. Result of the trade-off analysis show that ratio of water shortage at 26% will produce electricity energy of 3,6GWh/year with an area of rice fields that are not irrigated 260 Ha/year. The smaller short ratio, the greater discharge release so that electrical energy increase only if turbine head is available. Conversely, the greater discharge release, the smaller area of irrigated rice fields. The limit requirement of short ratio <30% in the simulation aims to prevent drought in the next period. This affect reservoir operating pattern for policy making that irrigation water cannot be flowed on demand in the month when inflow discharge is very small. This policy needs to be taken so that farmers have readiness to face drought. The simulation result show that in scenario 1 and 2 there are no irrigated rice fields for 3 months and 2 months, while in scenario 3 only for 1 months. Average drought occurs during the 2nd Planting Season (starting April-1) in the 8th and 9th months or at the end of harvest season. Final result of optimization analysis show best scenario 3 with average percentage of Demand Satisfaction (% DS) is 92.1% and produce energy per year of 2.6GWh. In addition, the result of the economic analysis of IRR were 34.31% and BCR 2.188. This shows that development of Sadawarna PLTMH is economically feasible. Electricity that produced will be connected to PT. PLN network to be further distributed to consumers. Water utilization efficiency can be applied to save water. Simulation shows there is water saving potential of 66.59 million m3/year to supply water requirements from Sadawarna Reservoir.